The Impact Of Performance-Based Budgeting Implementation On The Performance Accountability Of Government Agencies (Studi Empiris Pada Bapenda Kabupaten Sumedang) - Cahyani, Vini; Masruri, Fahrul Alam; Radia, Dewi Andita Permatasari; Ridwan, Zulkifli M (LPPM Universitas Sebelas April, 2025)
This study aims to determine the Implementation of Performance-Based Budgeting and Performance Accountability of Government Agencies and to determine how much influence the Implementation of Performance-Based Budgeting has on the Performance Accountability of Government Agencies at Bapenda Sumedang Regency. The research method used is a quantitative method with a Simple Linear Regression model. The sampling technique in this study used the purposive sampling method, while the data source was primary data by distributing questionnaires to 60 employees. The results showed that the variables had a positive and significant partial effect on the performance accountability of government agencies. The F value of 16.669 with a significance of 0.000 (<0.05) and R2 of 0.223 indicated that 22.3% of the variation in performance accountability of government agencies was explained by the implementation of performance-based budgeting. This study emphasizes the importance of implementing performance-based budgeting in supporting the performance accountability of government agencies